2020
DOI: 10.1177/2374373520959486
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Accelerates Need to Improve Online Patient Engagement Practices to Enhance Patient Experience

Abstract: The COVID-19 pandemic has led to rapid change in health care, accelerating the use of digital health services, including telehealth. Moreover, growth in value-based care has compelled consumers to become more engaged in care processes. It has also provided opportunities to enhance patient experiences by increasing patients’ access to online health information and services. This study assessed online patient engagement practices for 6 common patient touchpoints by reviewing the websites of the top 32 hospitals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 7 publications
0
25
0
3
Order By: Relevance
“…"Mild" COVID- 19. Patients indicated that they need information about the course and recovery of long-term "mild" symptoms without being hospitalized: "the news is mainly about the severe cases; information about 'mild' COVID-19 with persisting symptoms is limited."…”
Section: Care and Information Needsmentioning
confidence: 99%
“…"Mild" COVID- 19. Patients indicated that they need information about the course and recovery of long-term "mild" symptoms without being hospitalized: "the news is mainly about the severe cases; information about 'mild' COVID-19 with persisting symptoms is limited."…”
Section: Care and Information Needsmentioning
confidence: 99%
“…Tujuan dari pemberian informasi dan edukasi pasien adalah untuk mengkaji pengetahuan pasien tentang kesehatannya dan meningkatkan kesadaran pasien akan gejala/penyakit (Wong et al, 2018) Pasien harus mendapatkan informasi dan edukasi sesuai dengan kasus atau penyakit (Wong et al, 2018;Xu et al, 2018). Namun di masa pandemi Covid-19 ini memberikan informasi dan edukasi dapat dilakukan dengan cara memanfaatkan teknologi demi mengurangi transmisi terhadap tenaga kesehatan (Contreras et al, 2020;Li et al, 2015;Meyer, 2020;Srinivasan et al, 2020).…”
Section: Gambaran Pelibatan Pasien Dalam Asuhan Keperawatan DI Masa P...unclassified
“…Elemen pelayanan medis online, informasi pelayanan medis online, informasi interaktif online, pelayanan digital media, pelayanan informasi dengan resource berkualitas, pelayanan informasi dengan resource administrasi, pelayanan informasi berteknologi, serta desain informasi mempengaruhi efektivitas website rumah sakit. Meyer, 2020 [9]…”
Section: Hasil Dan Pembahasanunclassified
“…Konten dari website diharapkan juga selalu diperbaharui dengan informasi-informasi kesehatan terbaru dan juga membantu pemerintah di era pandemi COVID-19 dengan menghadirkan informasi yang benar dan tervalidasi [15][16][17]. Pelayanan rumah sakit yang ditampilkan dalam website rumah sakit, sebaiknya juga disertai dengan harga pelayanannya agar informasi semakin jelas bagi pasien dan calon pasien [2,9]. Elemen terakhir yang melindungi semua pelayanan pada website rumah sakit adalah keamanan website itu sendiri.…”
Section: Perçin 2019 [5]unclassified